Efeitos da L-arginina na proteção renal por meio da dosagem plasmática e urinária de biomarcadores e histologia: estudo em modelo experimental de lesão de isquemia e reperfusão em ratos sob anestesia inalatória - Bussmann, André Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Background: Nitric oxide (NO) inactivation occurs during renal ischaemia/reperfusion injury. This inactivation decreases endothelium-dependent and -independent arterial relaxation. Higher NO levels can improve endothelial dysfunction and arterial relaxation, thereby reducing the level of kidney injury. NO, synthesized from L-arginine by the enzyme nitric oxide synthase (NOS), seems to exerts a protective effect on the kidneys during tissue ischemia-reperfusion injury. The objective of this study was to evaluate the effect of L-arginine on the levels of injury biomarkers (pNGAL, uNGAL, KIM-1 e IL-18) for kidney function and histology in rats subjected ischaemiareperfusion injury. Methods: Thirty-two Wistar rats were randomised into the following 4 groups: Sham (S), laparotomy and right nephrectomy; Control (C), laparotomy and right nephrectomy and left kidney I/R; L-arginine control (LAC), laparotomy and right nephrectomy and L-arginine at a dose of 800 mg.kg-1 .dose-1 , 24 hours and 1 hour before surgery; and L-arginine (LA), laparotomy and right nephrectomy, left kidney I/R, and L-arginine at a dose of 800 mg.kg -1 .dose-1 , 24 hours and 1 hour before surgery. The pNGAL, uNGAL, KIM-1 e IL-18 and creatinine levels and kidney histopathology were analysed. The significance level was p < 0.05. Results: Creatinine was increased in all groups, with LA≈C>S≈LAC. pNGAL was increased in all groups and showed a similar trend. uNGAL levels were higher in groups C and LAC than LA and had intermediate values in group S. The KIM-1 levels were increased in the S, LAC and LA groups, but the contrast analysis revealed no differences between the groups in terms of their trends. IL-18 levels were higher in LA than in the other groups (C, S and LAC). The C and LA groups, compared with the S and LAC groups, had higher damage on the left side. There was no histopathological difference between C and LA or between S and LAC. Conclusion: L-arginine does not exert a damaging or protective effect on kidneys undergoing I/R injury based on the evaluation of kidney functions, histopathology and pNGAL and KIM-1 levels.

Justificativa: Durante lesão de isquemia e reperfusão renal ocorre a inativação de óxido nítrico (NO), essa inativação diminui o relaxamento arterial endotélio-dependente e independente. O aumento nos níveis de NO poderia melhorar a disfunção endotelial e o relaxamento arterial diminuindo a lesão renal. O NO, sintetizado a partir da L-arginina pela enzima óxido nítrico sintase (NOS), parece exercer um efeito protetor sobre os rins durante a lesão de isquemia/reperfusão (I/R). O objetivo do estudo foi avaliar o efeito da L-arginina nos níveis dos biomarcadores de lesão (NGALp, NGALu, KIM-1 e IL-18) na função e na histopatologia renal em ratos submetidos a lesão de I/R. Métodos: 32 ratos Wistar foram randomizados em 4 grupos: Sham (S): Laparotomia e nefrectomia direita. Controle (C): Laparotomia e nefrectomia direita, I/R em rim esquerdo. Controle L-arginina (CLA): Laparotomia e nefrectomia direita, L-arginina na dose de 800mg.kg-1.dose-1, 24 e 1 hora antes. L-arginina (LA): Laparotomia e nefrectomia direita, I/R em rim esquerdo, L-arginina na dose de 800mg.kg-1.dose-1, 24 e 1 hora antes. Foram analisados os níveis de NGALp, NGALu, KIM-1 e IL-18, creatinina e histopatologia renal. Nível de significância: p<0,05. Resultados: Creatinina aumenta em todos os grupos com LA≈C>S≈CLA. A NGALp, aumenta em todos os grupos com evolução semelhante. A NGALu foi maior no grupo C e CLA em relação ao grupo LA e apresentou valores intermediários no grupo S. Os níveis de KIM-1 aumentam nos grupos S, CLA e LA, porém na análise de contrastes não há diferença na evolução dos grupos. A IL-18 apresentou valores maiores no grupo LA comparado aos demais grupos (C, S e CLA). Os grupos C e LA apresentaram grau de lesão no lado esquerdo maior que os grupos S e CLA. Não existe diferença histopatológica entre C e LA e nem entre S e CLA. Conclusão: A L-arginina não exerce efeito protetor ou danoso aos rins submetidos a lesão de I/R na avaliação da função, da histopatologia renal e dos níveis de NGALp, KIM-1
The effects of L-arginine in renal protection using urinary and serum biomarkers levels and histopathologic features: experimental model study of ischemia/reperfusion injury in rats under inhalatory anesthesia
Keywords: Reperfusion; Ischemia; Acute kidney injury; L-arginine; L-arginina; NGAL; KIM-1; IL-18; Isquemia; Lesão renal aguda